Migration in times of the Second World War. The case of a Jewish woman in Tucumán (2021)
The purpose of this article is to analyse the migratory movement of Jewish refugees caused by the Second World War and Nazi violence. For this, the present work reconstructs and examines the journey of a Jewish woman who escaped from Poland and who sought refuge in Argentina, around the year 1941. From the perspective of social history and with a qualitative methodology, the work explores, though her travel log, her feelings and reflections regarding the relatives who had remained in Europe, the dramatic consequences of the war and the forced migrations. Her expressions of gratitude for the help she received during her migratory journey, as well as, in contrast, her negative opinions about certain attitudes and policies (for example those of the Soviet Union) draw upon her migration experiences, set in a key phase of the advancement of the Nazi terror, before the establishment of the so called «Final solution». Another situation that underlies this work revolves around the feeling of sorrow and the weight that came from her being the only member of her family that was saved, a   concern common to other refugees and Jewish survivors of the Shoá.